(untitled) (International Journal of Engineering and Computer Science, 2015)
Although tremendous progress has done in past years on memory designing but still Radiation-induced soft errors is concerned area in the field of soft memories and the single error correction double error detection (SEC-DED) codes are commonly used to give assured memory contents with absence of corrupted scenario. Since SEC-DED codes cannot correct multiple errors, they are often combined with interleaving. Interleaving, however, impacts memory design and performance and cannot always be used in small memories. This limitation has spurred interest in codes that can correct adjacent bit errors. In particular, several SEC-DED double adjacent error correction (SEC-DED-DAEC) codes have recently been proposed. Implementing DAEC has a cost as it impacts the decoder complexity and delay. Another issue is that most of the new SEC-DED-DAEC codes miscorrect some double nonadjacent bit errors. In this brief, a new class of SEC-DED-DAEC codes is derived from orthogonal Latin squares codes. The new codes significantly reduce the decoding complexity and delay. In addition, the codes do not miscorrect any double nonadjacent bit errors. The main disadvantage of the new codes is that they require a larger number of parity check bits. Therefore, they can be useful when decoding delay or complexity is critical or when miscorrection of double nonadjacent bit errors is not acceptable. The proposed codes have been implemented in Hardware Description Language and compared with some of the existing SEC-DED-DAEC codes. Finally the experimental results confirm the reduction in decoder delay.